Unresolved resonance parameter evaluation and uncertainty quantification of n + 181Ta reactions - Jesse M. Brown; Devin P. Barry; Amanda Lewis; Timothy H. Trumbull; Marco T. Pigni; Travis Greene; Robert C. Block; Alec Golas; Yaron Danon (Annals of Nuclear Energy, 2025)

Multi-Decadal High-Resolution Data Reveal the Cryptic Vertical Movement Patterns of a Large Marine Predator Along the Californian Coast - Samantha Andrzejaczek; Taylor K. Chapple; Salvador J. Jorgensen; Scot D. Anderson; Michael Castleton; Paul E. Kanive; Timothy D. White; Barbara A. Block (Frontiers in Marine Science, 2022)
Over the last two decades, satellite tagging of adult and sub-adult white sharks Carcharodon carcharias off the west coast of North America has revealed a predictable onshore-offshore migratory cycle. Our current understanding of the vertical movements exhibited by white sharks while in their coastal foraging phase in the California Current, however, remains limited. Here, we used recovered datasets from 31 archival satellite tags to quantify vertical habitat use. Tags were deployed on individuals between 2000 and 2018 and recorded depth and temperature data at continuous 1–120 s intervals before being recovered up to a year after deployments. Four satellite-tagged individuals were concurrently tagged with acoustic tags, providing precise location data when detected by acoustic receivers that allowed us to explore how reported vertical habitat use varied spatially. While in the coastal shelf waters, white sharks moved at a mean depth ± SD of 14.3 ± 4.0 m and occupied significantly deeper depths during the day than the night. High individual, temporal and spatial variation was evident in vertical movements, while consistent diel and lunar effects emphasized the importance of light-level driving vertical behavior around hunting sites. The vertical movement behaviors reported here provide knowledge of how white sharks may directly and indirectly interact with their mammalian prey in a dynamic three-dimensional system during their capital foraging phase. Temporal patterns in vertical behavior, for instance, indicated that surface waters during early morning hours are the riskiest place for prey. Combining these novel findings with higher-resolution biologging techniques in future studies will allow us to further contextualize fine-scale vertical movement behaviors of white sharks and examine the specific foraging events that could not yet be isolated in the tagging data.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

Tracking the response of industrial fishing fleets to large marine protected areas in the Pacific Ocean - Timothy D. White; Tiffany Ong; Francesco Ferretti; Barbara A. Block; Douglas J. McCauley; Fiorenza Micheli; Giulio A. De Leo (Conservation Biology, 2020)
Large marine protected areas (MPAs) of unprecedented size have recently been established across the global oceans, yet their ability to meet conservation objectives is debated. Key areas of debate include uncertainty over nations’ abilities to enforce fishing bans across vast, remote regions and the intensity of human impacts before and after MPA implementation. We used a recently developed vessel tracking data set (produced using Automatic Identification System detections) to quantify the response of industrial fishing fleets to 5 of the largest MPAs established in the Pacific Ocean since 2013. After their implementation, all 5 MPAs successfully kept industrial fishing effort exceptionally low. Detected fishing effort was already low in 4 of the 5 large MPAs prior to MPA implementation, particularly relative to nearby regions that did not receive formal protection. Our results suggest that these large MPAs may present major conservation opportunities in relatively intact ecosystems with low immediate impact to industrial fisheries, but the large MPAs we considered often did not significantly reduce fishing effort because baseline fishing was typically low. It is yet to be determined how large MPAs may shape global ocean conservation in the future if the footprint of human influence continues to expand. Continued improvement in understanding of how large MPAs interact with industrial fisheries is a crucial step toward defining their role in global ocean management.

Calcium Phosphate Particles as Pulmonary Delivery System for Interferon-α in Mice - Tülin Morçöl; Jessica M. Weidner; Anand Mehta; Stephen J.D. Bell; Timothy Block (AAPS PharmSciTech, 2018)

Direct evidence that HSV DNA damaged by ultraviolet (UV) irradiation can be repaired in a cell type-dependent manner - Scott Millhouse; Xiaohe Wang; Nigel W. Fraser; Lisa Faber; Timothy M. Block (Journal of NeuroVirology, 2012)

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Two Cases of Recovery of Dimorphic Pathogenic Fungi via Conventional BacT/ALERT® Microbial Detection System Media - Erik Munson; Tina Endes; Katharine Vaughan; Timothy Block; Jeanne E. Hryciuk (Mycopathologia, 2009)

Tumor-associated protein SPIK/TATI suppresses serine protease dependent cell apoptosis - Xuanyong Lu; Jason Lamontagne; Felix Lu; Timothy M. Block (Apoptosis, 2008)

Herpes simplex virus type 1 ICP4 deletion mutant virus d120 infection failed to induce apoptosis in nerve growth factor–differentiated PC12 cells - Benjamas Aiamkitsumrit; Xianchao Zhang; Timothy M Block; Pamela Norton; Nigel W Fraser; Ying-Hsiu Su (Journal of NeuroVirology, 2007)

The stability of herpes simplex virus type I genomes in infected Vero cells undergoing viral induced apoptosis - Ying-Hsiu Su; Xianchao Zhang; Benjamas Aiamkitsumrit; Qiyi Tang; Gerd Maul; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2006)